Kadar Timbal pada Rambut Supir Truk - Zahran Arya Zidan; Teguh Budiharjo (Poltekkes Kemenkes Semarang, 2021)
Heavy metal lead can cause poisoning or accumulate in human body. Truck drivers spend more a lot of time on the road due to the slow movement of trucks due to carrying heavy loads causing exposure to lead on the highway. Lead enters through the breath and is excreted in the hair. Truck drivers spend more a lot of time on the road, especially trucks that have more than 4 wheels because the load they carry is heavy so it takes time to travel and can be exposed lead on the road. It also allows researchers to easily collect hair samples. longer the work, they get higher lead levels in the human body. After conducting a survey, many truck drivers opened their windows. This happens, maybe some of the Air Cooler (AC) trucks are not working because maybe some of the trucks are too old. This allows truck drivers to be exposed to lead from the air. In addition, PPE (Personal Protective Equipment) is also important such as masks to reduce exposure to lead from the respiratory tract.